DIAGNOSING VON HIPPEL LINDAU DISEASE BY RETINAL CAPILLARY HAEMANGIOBLASTOMAS - Yurike Mandrasari; Wino Vrieda Vierlia; Andhika Yudistira; Nadia Artha Dewi (International Journal of Retina, 2022)
Introduction: Von Hippel-Lindau (VHL) syndrome is a disease characterized by the formation of tumors or cysts in many different parts of the body caused by germline. The prevalence of this autosomal dominant condition is very rare. Understanding of clinical manifestasion and diagnostic criteria is needed. Case Report: Female, 22-year-old was reffered from orthopaedic department suffered from blurred and misalignment of the left eye since 3 months ago . Based on indirect funduscopy examination, we found disc swelling with exudative retinal detachment on her left eye and orange-reddish retinal mass concluded as Retinal Capillary Hemangioblastoma (RCH) with tortuosity and dilatation of blood vessel on her right eye. The MRI showed multiple masses in cervical to lumbar vertebrae and multiple cyst on pancreatic gland. Discussion: This patient had 1 ocular RCH, multiple spinal tumor and multiple pancreatic cysts with no confirmed family history, therefore almost fulfilling the diagnostic criteria of VHL. To further confirm the diagnosis, it was necessary to find other common comorbids of VHL such as gene testing of VHL heterozygous germline mutation. Interdisciplinary approach consists of not only diagnostic and treatment plans from one speciality department, but also the ones from other related divisions and departments. Conclusion: Screening and interdiciplinary approach in managing Von Hippel-Lindau syndrome are required to be performed promptly.